2011
DOI: 10.1186/cc9966
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acetate, gluconate and interleukin-6 profiles during and after cardiopulmonary bypass: a comparison of Plasma-Lyte 148 with a bicarbonate-balanced solution

Abstract: IntroductionAs even small concentrations of acetate in the plasma result in pro-inflammatory and cardiotoxic effects, it has been removed from renal replacement fluids. However, Plasma-Lyte 148 (Plasma-Lyte), an electrolyte replacement solution containing acetate plus gluconate is a common circuit prime for cardio-pulmonary bypass (CPB). No published data exist on the peak plasma acetate and gluconate concentrations resulting from the use of Plasma-Lyte 148 during CPB.MethodsThirty adult patients were systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
1
21
2
1
Order By: Relevance
“…Although IL-6 levels did not differ significantly in this study the author concluded that one cannot rule out that these supra-physiological anion levels can be harmful [22]. Acetate has been shown to stimulate cytokine release such as IL-1, to cause carbohydrate intolerance and disturbance of fatty acid synthesis [23].…”
Section: Discussionmentioning
confidence: 59%
“…Although IL-6 levels did not differ significantly in this study the author concluded that one cannot rule out that these supra-physiological anion levels can be harmful [22]. Acetate has been shown to stimulate cytokine release such as IL-1, to cause carbohydrate intolerance and disturbance of fatty acid synthesis [23].…”
Section: Discussionmentioning
confidence: 59%
“…Those with a greater degree of acidosis received CSL more commonly than sodium chloride, presumably because of the perceived risk of worsening the acid–base status by promoting hyperchloraemic metabolic acidosis due to the lower chloride content in CSL. Another proposed hypothesis for the delay in resolution of DKA is that CSL contains lactate which requires additional metabolism in the liver . Data on lactate were not collected in this study and would be of interest in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Small quantities of acetate in dialysate solutions have been reported to cause supra-physiological acetate plasma concentrations (50 to 100 μmol/L)[47-49]. In addition, use of acetate solutions as a cardiopulmonary prime has also been reported to cause similar plasma concentrations in patients undergoing cardiac surgery[50], although it is unknown if such concentrations are associated with detrimental or adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The unmeasured anions were attributed to acetate and gluconate. Davies et al[50] observed that when PL 148 was administered as a cardiopulmonary bypass pump-prime fluid, there were supra-physiologic plasma levels of acetate and gluconate when compared to a bicarbonate pump prime solution. There were no significant differences in systemic inflammation (as measured by Interleukin-6 levels), and the authors advocated larger scale studies to more precisely assess this phenomenon.…”
Section: Discussionmentioning
confidence: 99%